Uma avaliação do Projeto Saúde, Bombeiros e Sociedade na promoção da Saúde de Idosos no Ceará - Albuquerque, Eliane Regina Oliveira (2018)
INTRODUCTION: Aging is seen as one of the public health problems affecting all populations. Demographic change and increasing average life expectancy pose a number of challenges to individuals and society. These include the promotion of active and healthy aging to guarantee the rights of the elderly. In this context, the State of Ceará Military Fire Department develops the Health, Fire and Society project, which aims to reach people aged 60 and over, provide them with an opportunity to take care of biopsychosocial health through participation in groups of multidisciplinary activities. Thus, this study intends to contribute to the understanding of the strategies carried out in order to promote the health and quality of life of the elderly, to generate subsidies to promote improvements in care for the elderly. OBJECTIVE: To evaluate the activities of the Health, Firefighters and Society Project in the promotion of health and quality of life of the elderly: The case of the nucleus Happy Sunset. METHOD: Qualitative research, a case study developed in the "Happy Sunset" nucleus of the Health, Firefighter and Society Project of the Military Fire Brigade of the State of Ceará. The subjects of the study were the 18 elderly and the 05 firemen (1 general coordinator and 4 monitors) that are part of the Project. The interviews were carried out in June and July 2017, the material collected and transcribed generated 90 pages being analyzed according to the technique of Content Analysis. The study was submitted to the Ethics in Research Committee (CEP) with approved opinion No. 2,077,157. RESULTS AND DISCUSSION: Characterization of the subjects of the study was carried out and 03 categories emerged: Changes and improvement of the health conditions of the elderly that discusses the benefits of the project activities in the subjects' quality of life; Formation of affective bonds with the group focusing on the importance of social support and the integration that persists during the activities and Structure and Evaluation of the Project: Benefits and difficulties presents the course for implementation, the challenges of budget and human resources for maintenance of the nucleus. FINAL CONSIDERATIONS: It was verified that the profile of the participants was mostly women, married with incomplete elementary school, retired, housewives and monthly income of up to a minimum wage. The activities of the group changed life, reducing pain and tiredness and more autonomy in the day to day, there is a very strong affective bond in the nucleus between the participants and the firemen strengthening social support.